2004
DOI: 10.1038/nm1099
|View full text |Cite
|
Sign up to set email alerts
|

The 5-lipoxygenase pathway promotes pathogenesis of hyperlipidemia-dependent aortic aneurysm

Abstract: Activation of the 5-lipoxygenase (5-LO) pathway leads to the biosynthesis of proinflammatory leukotriene lipid mediators. Genetic studies have associated 5-LO and its accessory protein, 5-LO-activating protein, with cardiovascular disease, myocardial infarction and stroke. Here we show that 5-LO-positive macrophages localize to the adventitia of diseased mouse and human arteries in areas of neoangiogenesis and that these cells constitute a main component of aortic aneurysms induced by an atherogenic diet conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
290
3
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 315 publications
(310 citation statements)
references
References 49 publications
16
290
3
1
Order By: Relevance
“…For example, we demonstrated that deficiency of the gene encoding 5-lipoxygenase (Alox5) in mice protects against the development of aortic lesions [3,4], and that promoter variants of the human ALOX5 gene are associated with increased carotid intima-media thickness [5]. Other groups have also reported findings that support the involvement of the 5-LO/LT pathway in CVD traits [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 88%
“…For example, we demonstrated that deficiency of the gene encoding 5-lipoxygenase (Alox5) in mice protects against the development of aortic lesions [3,4], and that promoter variants of the human ALOX5 gene are associated with increased carotid intima-media thickness [5]. Other groups have also reported findings that support the involvement of the 5-LO/LT pathway in CVD traits [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 88%
“…In a cholate diet-triggered model of AAA, 5-LO deficiency strikingly diminished aneurysmal dilation in a hyperlipidemic mouse background (10). The study demonstrated that 5-LO ϩ macrophages localize to the adventitia of diseased mouse arteries and constitute a main component of aortic aneurysms.…”
Section: Discussionmentioning
confidence: 74%
“…Thus, deletion of BLT1 appears to prevent leukotriene-induced increases in vascular wall MCP-1 expression in vivo. Zhao et al (10) found that 5-LO deficiency significantly attenuates plasma MIP-1␣, another monocyte chemoattractant associated with vascular pathology. We found a marked reduction in MIP-1␣ in the suprarenal aortas of Ang II-treated Apoe Ϫ/Ϫ / Blt1 Ϫ/Ϫ mice as compared with those from the Ang II-treated Apoe Ϫ/Ϫ controls consistent with this prior study (Fig.…”
Section: Decreased Proinflammatory Cytokine Levels In Apoementioning
confidence: 99%
“…5 Modifier genes such as 5,10-methylenetetrahydrofolate reductase (MTHFR) help to identify patients who have a high probability of developing severe manifestations of the disease. 8 Susceptibility genes, such as MTHFR, 9 metalloproteinase-9, 10 chemokine receptor 5 (CCR5) 11 5-lipoxygenase (5-LO), 12 carrying polymorphic mutations such as C677T MTHFR, C1562T MMP9, ∆32 CCR5, [11][12][13] predispose to abdominal aortic aneurysms (AAA) and/or atherosclerosis.…”
mentioning
confidence: 99%
“…In addition, Hcy may directly affect fibrillin-1 or collagen by interfering with intra-and/or intermolecular disulfide bonds through disulfide exchange, or binding to free sulphydryl groups. If the usefulness of including Hcy determination in the clinical evaluation is confirmed, it will be possible to identify the potential candidates for a vitamin supplementation using folic acid, or vitamins B 6 or B 12 .…”
mentioning
confidence: 99%